THE UTILIZATION OF FLY ASH ON THE GROWTH OF AND PRODUCTION OF THE SWEET CORN ON PEAT SOIL - Togatorop, Marthin Jonathan; Darussalam, Darussalam; Gusmayanti, Evi (Jurnal Sains Mahasiswa Pertanian, 2019)
This experiment aims to analyze the influence the aplicationn of fly ash at peat on the growth and crop sweet corn production. The experiment was done on peat soil at district Southeastern Pontianak, from March - May 2018. Experimental design used was complete block design one factor of treatment waste coal (fly ash) with 5 treatment, p1 = 0.75 kg per plot, p2 = 4.9 kg per plot, p3 = 8.9 kg per plot, p4 = at kg per plot, p5 = 17,02 kg per plot. All treatment to replication 5 time, the result that there are 25 plot experiment.Variable examined were long plant, dry weight, corn weight husk, corn weight without husk, corn lenght, corn diameter, plant diameter and variable supporting is temperature, humidity and precipitaion. The results of the study showed that treatment was no significant effect in all statistical variabel observation.Key word : Fly ash, Peat soil, Sweet corn,